2020
DOI: 10.1101/2020.05.30.124958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Herpes Simplex Virus type 1 neuronal infection triggers disassembly of key structural components of dendritic spines

Abstract: Herpes simplex virus type 1 (HSV-1) is a widespread neurotropic virus. The primary infection in facial epithelium leads to retrograde axonal transport to the central nervous system (CNS) where it establishes latency. Under stressful conditions, the virus reactivates, and new progeny is transported anterogradely to the primary site of infection. In late stages of neuronal infection, axonal damage is known to occur. However, the impact of HSV-1 infection on morphology and functional integrity at earlier stages o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…It has been previously reported that lytic HSV-1 neuronal infection causes synaptic dysfunction, associated with disassembly of key structural components of dendritic spines and upregulation of activity-regulated cytoskeleton-associated protein (ARC) mRNA and protein expression (29, 30). In our system, we observed massive downregulation of major pre- and postsynaptic components, including synaptic vesicle genes ( SV2A , SV2B , SYP, VAMP2 ) and genes that function in calcium signaling ( SYT13 , CAMK2A , CAMK2B , CALB2 ) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that lytic HSV-1 neuronal infection causes synaptic dysfunction, associated with disassembly of key structural components of dendritic spines and upregulation of activity-regulated cytoskeleton-associated protein (ARC) mRNA and protein expression (29, 30). In our system, we observed massive downregulation of major pre- and postsynaptic components, including synaptic vesicle genes ( SV2A , SV2B , SYP, VAMP2 ) and genes that function in calcium signaling ( SYT13 , CAMK2A , CAMK2B , CALB2 ) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%